An Innovative Structural Solution to Failed Stabilized Earth Embankment in Multilevel Interchange - Kara, Ali; Tahoun, Tamer (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper summarizes a case study of a failure in a mechanically stabilized earth retaining wall ramp heading to a multilevel interchange. The failure was caused by a washout cavity resulting from a long-term leakage from unknown existing wet utilities adjacent to the mechanically stabilized earth retaining wall. The interchange is located within a very congested traffic area and has limited right of way and working space. The methodology of investigation, root cause of the failure, evaluation of the existing structure and innovative solution to the problem within fast-track design and construction are studied in this paper. Due to the necessity of maintaining the existing traffic movements at the interchange which is located at one of the most important expressway routes, timely rectification methodology was conceived, designed and implemented. This paper is prepared only to evaluate the technical innovative alternatives, solutions and fast-track construction without mentioning the interchange and project area.